PP-O and PP-V, Monascus pigment homologues, production, and phylogenetic analysis in Penicillium purpurogenum. Issue 12 (December 2015) - Arai, Teppei; Kojima, Ryo; Motegi, Yoshiki; Kato, Jun; Kasumi, Takafumi; Ogihara, Jun
Abstract: The production of pigments as secondary metabolites by microbes is known to vary by species and by physiological conditions within a single strain. The fungus strain Penicillium purpurogenum IAM15392 has been found to produce violet pigment (PP-V) and orange pigment (PP-O), Monascus azaphilone pigment homologues, when grown under specific culture conditions. In this study, we analysed PP-V and PP-O production capability in seven strains of P. purpurogenum in addition to strain IAM15392 under specific culture conditions. The pigment production pattern of five strains cultivated in PP-V production medium was similar to that of strain IAM15392, and all violet pigments produced by these five strains were confirmed to be PP-V. Strains that did not produce pigment were also identified. In addition, two strains cultivated in PP-O production medium produced a violet pigment identified as PP-V. The ribosomal DNA (rDNA) internal transcribed spacer (ITS) region sequences from the eight P. purpurogenum strains were sequenced and used to construct a neighbor-joining phylogenetic tree. PP-O and PP-V production of P. purpurogenum was shown to be related to phylogenetic placement based on rDNA ITS sequence. Based on these results, two hypotheses for the alteration of pigment production of P. purpurogenum in evolution were proposed.